Absence of association between host genetic mutations in the ORAI1 gene and COVID-19 fatality. - Heba Shawer; Chew W Cheng; Marc A Bailey (PLoS ONE)
The calcium ion channel ORAI1 has emerged as a promising therapeutic target for the Coronavirus Disease 19 (COVID-19)-associated pneumonia, and a pharmacological inhibitor of ORAI1 has now reached clinical trials for severe COVID-19 pneumonia. Whether ORAI1 itself is associated with an increased risk for severe COVID-19 presentation is still unknown. Here, we employed genetic association analysis to investigate the potential association of host genetic polymorphisms of ORAI1 with the risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and its associated COVID-19 fatality in UK Biobank participants from white British background. The analysis showed no significant association between ORAI1 variants and COVID-19 positivity or fatality, despite the well-established roles of ORAI1 in immune response and inflammation and the success of ORAI1 inhibition in clinical trials. Our results suggest that the host genetic polymorphisms of ORAI1 are unlikely to be implicated in the broad variability in symptoms severity among afflicted patients.